Design of Mobile Healthcare Reminder for Chronic Diabetes - Al-Hasnawi, Sarah; Ahmad, Mazida; Al-Janabi, Ammar; Zulkifli, Abdul Nasir; Omar, Mazni; Abu Bakar, Juliana Aida (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2016)
Mobile technology has been increasingly used in healthcare services. However, little has been done in handling patients of chronic disease. Accordingly, this study aims to design a mobile reminder system that cares for patients’ selfmanagement of their chronic diabetes. To achieve the main aim, the following sub objectives have been formulated; (i) to identify the requirements for the mobile healthcare reminder suitable for chronic diabetes, (ii) to develop and construct the prototype of the system, (iii) to evaluate the prototype in terms of perceived usefulness, perceived ease of use, and satisfaction. The prototype has been evaluated using an adapted questionnaire, involving 30 patients in Baghdad Hospital. The results reveal that the prototype is perceived useful and easy to use by the participants. Also, they are highly satisfied with the prototype. The outcome of this study would help mobile healthcare applications developers to design future mobile reminder system particularly for patients who are suffering from chronic disease